Evaluation of an Anthrax Epidemic in Eastern Türkiye and Source Control - Tartar, Ayse Sagmak; Tuncer, Kevser; Kaygusuz, Turkkan Ozturk; Asan, Mehmet Ali; Akbulut, Ayhan; Demirdag, Kutbeddin (Bilimsel Tip Yayinevi, 2024)
Introduction: The present study reports anthrax cases who presented to F & imath;rat University Hospital, and provides details of the surveillance data, contact tracing, and efforts to break the infection chain with an analysis of the garnered data. Materials and Methods: A total of 174 individuals who had been in contact with two infected animals during and after their slaughter, whether through direct skin contact or exposure to their intestinal tract, were included in the study examining a recently identified anthrax outbreak in two locations within the city of Mul, Eastern T & uuml;rkiye. Results: A patient presented to our center with a preliminary diagnosis of ophthalmic periorbital cellulitis/necrotizing fasciitis. Following a preliminary diagnosis of anthrax, gram-positive bacilli were identified in the Gram stain of a sample obtained from the lesion, and the microbiological diagnosis was confirmed. An outbreak evaluation report was subsequently produced based on all the collected data. The outbreak was found to originate from two sources, 8.5 km apart, in two locations in the same city. Among the total 174 contact persons in two locations were, eight women (five nursing), one pregnant woman and two babies. The median age of the hospitalized patients was 41 years (24-71). Of the hospitalized patients, two were female (20%) and eight (80%) were male. Furthermore, seven were animal breeders (70%), two were housewives (20%) and one was a government official (10%). Contact was through the skin and the gastrointestinal system in ten (100%) patients. Lesions were on the face in one (10%) and in the upper extremity in nine Conclusion: A leading factor in prevention and infection control is to ensure coordination among all involved institutions. The Directorate of Agriculture in the city initiated animal vaccinations, and the region was placed under quarantine to prevent the entry or exit of infected animals until the outbreak subsided. Since anthrax spores can survive in soil for a long time, the most effective approach to preventing anthrax in both humans and animals is vaccination.
Keywords: Anthrax; Endemic; Outbreak